EFFECT OF LONG-TERM ENOXAPARIN THERAPY ON RISK OF RECURRENT VENOUS THROMBOEMBOLIC COMPLICATIONS AND RECANALIZATION OFTHROMBOSED VEINS - N. M. Vorobyova; O. V. Ermolina; T. V. Balakhonova; A. I. Kiriyenko; E. P. Panchenko («REMEDIUM GROUP» Ltd., 2015)
The article presents the results of its own study of the effect of long-term (not less than 30 days) enoxa-parin therapy (1 mg/kg administered subcutaneously every 12h) on the risk of recurrent venous thromboembolic complications (VTC) and recanalization of thrombosed deep veins. The enoxaparin therapy was compared with a standard approach to treatment (unfractionated heparin for not less than 5 days followed by the administration of warfarin). The extended enoxaparin therapy was significantly more effective than standard treatment due to its impact on the risk of recurrent deep vein thrombosis (DVT) and recanalization of thrombosed deep veins. On top of that, the effect of enoxaparin in the first month of treatment of VTC episodes last for the next 11 months. As a result, the extension of enoxaparin therapy was associated with an 88% reduction in the risk of DVT recurrence during 12 months of anticoagulant therapy and a 2.5-fold increase in the probability of recanalization of venous occlusions by the end of the first year of treatment compared with the standard therapy with unfractionated heparin and warfarin.